Increased Risk of Stroke in Patients With Fibromyalgia: A Population-BASED Cohort Study. Issue 8 (February 2016) - Tseng, Chun-Hung; Chen, Jiunn-Horng; Wang, Yu-Chiao; Lin, Ming-Chia; Kao, Chia-Hung
Abstract : Abstract: Neuropsychiatric diseases might enhance stroke development, possibly through inflammation and atherosclerosis. Approximately 25% to 40% of patients with stroke, largely younger patients, are not associated with any conventional stroke risk factors. In this research, we explored whether fibromyalgia (FM), a neuropsychosomatic disorder, increases stroke risk. From a claims dataset with one million enrollees sourced of the Taiwan National Health Insurance database, we selected 47, 279 patients with FM and randomly selected 189, 112 age- and sex-matched controls within a 3-year period from January 1, 2000 to December 31, 2002. Stroke risk was assessed using Cox proportional hazards regression. Comorbidities associated with increased stroke risk, such as hypertension, diabetes, hyperlipidemia, coronary heart disease, irritable bowel syndrome, and interstitial cystitis, were more prevalent in patients with FM and high stroke risk than in the controls. The overall stroke risk was 1.25-fold (95% confidence interval [CI]: 1.21–1.30) higher in the FM group than in the non-FM group. Even without comorbidities, stroke risk was higher in patients with FM than in the controls (adjusted hazard ratio [aHR] = 1.44, 95% CI: 1.35–1.53, P  < 0.001). The relative risk of stroke was 2.26-fold between FM and non-FM groups in younger patients (age <35 years, 95% CI: 1.86–2.75). This is the first investigation associating FM with an increased risk of stroke development. The outcomes imply that FM is a significant risk factor for stroke and that patients with FM, particularly younger patients, require close attention and rigorous measures for preventing stroke.